Isokinetic upper body strength testing - a useful tool for diagnostics and classification in paralympic sit skiing? - Olvermann, M.; Spitzenpfeil, P.; Goll, M. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: In Paralympic sit-skiing and Olympic skiing athletes are striving for the same goals: medals and success. As the profile of a sport defines the training content the question is if those profiles are similar. Goll et al. (2014) have shown some differences concerning metabolism and, due to the nature of sit skiing, in muscles used. In Olympic skiing maximum core strength and stability are important factors whereas in Paralympic sit skiing movement quality, motor control and coordination are of high importance to ski fast and control the monoski. The aim of the study was to explore whether a standard core strength protocol for Olympic athletes can be applied to Paralympic sit skiers and whether data derived can serve as a basis for training recommendations or support in classification.